Effectiveness of E-Learning Approach to Contextual Teaching and Learning in Improving Students ′Ability. Issue 1 (February 2021) - Azhar, Zulfi; Suparno,; Rukun, Kasman; Jama, Jalius; Effendi, Hansi; Muskhir, Mukhlidi
Abstract: In this study using a contextual teaching and learning approach to STMIK Royal Kisaran students. Class sampling consisted of class SI-5C using the CTL approach and class SI-5F using CTL and e-learning as an experimental group, while the class SI-5D used a conventional approach as a control group. Using the pretest and posttest in the form of multiple choice as instruments in artificial intelligence lectures. From the results of the tests carried out there are significant differences in students who are taught using the CTL and E-learning approaches and conventional approaches. Taking approaches of CTL and CTL & E-Learning to students is more effective than conventional ones. However, CTL is better than using the approach of CTL & E-Learning.